Design of a fully wireless indoor smart energy saving and monitoring system - Li, Woon Koay; Naif, Yasir Hashim (2018)
The wireless indoor smart technology has changed rapidly and improved daily living. Humans will continue to enjoy comfortable and convenient lives with the support of the latest technology. The proposed Smart Energy Saving and Monitoring System (SESMS) was designed and developed to control the operations of indoor electrical appliances, especially in offices. SESMS is wireless and fully automated, and it reduces power consumption, particularly in high power consuming sectors, such as commercial and industrial areas. SESMS includes a monitoring system that can analyze the data collected from various conditions, thereby avoiding electricity wastage. The interface of the Monitoring Control System was designed to collect data easily and to show the information clearly to users. The collected data will display clearly and automatically in Microsoft Excel. The interface of the monitoring system indicates the status of every office according to the data collected.